Gender, continuity, and the shaping of modernity in the arts of East Asia, 16th-20th centuries - Chiem, Kristen L.; Blanchard, Lara C. W. (Gendering the trans-Pacific world, 2017)
This book explores women's and men's contributions to the arts and gendered visual representations in China, Korea, and Japan from the premodern through modern eras. A critical introduction and nine essays consider how threads of continuity and exchanges between the cultures of East Asia, Europe, and the United States helped to shape modernity in this region, in the process revealing East Asia as a vital component of the trans-Pacific world. The essays consider examples of architecture, painting, woodblock prints and illustrated books, photography, and textiles.